THE EFFICACY OF ICE-BREAKING ACTIVITIES IN ENHANCING STUDENTS' MOTIVATION FOR ENGLISH LANGUAGE ACQUISITION - Zulfadli, Noratul Emi; Farizawati; Jamaliah (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
Ice breaking is believed to cultivate a pleasant learning environment and promote active student participation. It's essential to note that the effectiveness of the ice-breaking strategy hinges on the teacher's ability to craft and execute the activity. Teachers must demonstrate creativity and innovation when selecting ice-breaking activities that align with student characteristics and lesson material. This research aims to explore the application of ice-breaking activities in the learning process to enhance students' motivation at Beuah State Elementary School. The study adopts a descriptive qualitative approach focusing on an English teacher as the key informant. Data collection methods include interviews and documentation, while data analysis incorporates data reduction, presentation, and conclusion techniques. The findings suggest that incorporating ice-breaking activities into learning sessions has transformed the previously dull and uninspiring atmosphere into a vibrant and enjoyable one, increasing student motivation. As a result, ice-breaking activities are deemed highly effective in boosting student engagement and motivation.